2021
DOI: 10.1038/s41390-021-01660-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 acquisition and immune pathogenesis among school-aged learners in four diverse schools

Abstract: Background Understanding SARS-CoV-2 infection in children is necessary to reopen schools safely. Methods We measured SARS-CoV-2 infection in 320 learners [10.5 ± 2.1 (sd); 7–17 y.o.] at four diverse schools with either remote or on-site learning. Schools A and B served low-income Hispanic learners; school C served many special-needs learners, and all provided predominantly remote instruction. School D served middle- and upper-income learners, with predomin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…80 It has been shown that schools with multi-layered precautions and/or mask mandates have been more successful at limiting SARS-CoV-2 spread in classes and/or campuses and limiting outbreaks. 8183 Nevertheless, even though observations have been somewhat reassuring regarding a similar level of transmission in schools as in the community, some demonstrating even lower rates in children enrolled in on-site classes, 24, 84, 85 several reports point to increases in county-level COVID-19 incidence following outbreaks at colleges with in-person instructional formats, 86, 87 perhaps also indicative of differences between K-12 schools and higher educational settings. Further, during the period of our study COVID-19 vaccines were not yet authorized.…”
Section: Discussionmentioning
confidence: 99%
“…80 It has been shown that schools with multi-layered precautions and/or mask mandates have been more successful at limiting SARS-CoV-2 spread in classes and/or campuses and limiting outbreaks. 8183 Nevertheless, even though observations have been somewhat reassuring regarding a similar level of transmission in schools as in the community, some demonstrating even lower rates in children enrolled in on-site classes, 24, 84, 85 several reports point to increases in county-level COVID-19 incidence following outbreaks at colleges with in-person instructional formats, 86, 87 perhaps also indicative of differences between K-12 schools and higher educational settings. Further, during the period of our study COVID-19 vaccines were not yet authorized.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk of severe disease or death is relatively low in hospitalized patients with Omicron. In Canada, Omicron infected cases have a 65% lower risk of hospitalization or death than Delta infections 59 . In vitro studies revealed that Omicron replicated faster than Alpha, Beta, and Delta 60 .…”
Section: Characteristics Of Sars‐cov‐2 Variantsmentioning
confidence: 99%
“…In Canada, Omicron infected cases have a 65% lower risk of hospitalization or death than Delta infections. 59 In vitro studies revealed that Omicron replicated faster than Alpha, Beta, and Delta. 60 Interestingly, the replication competence of Omicron in human alveolar cells was significantly lower than that of Delta, 60 which might explain the reduced severity of Omicron.…”
Section: Clinical Features Of Sars-cov-2 Variant-induced Covid-19mentioning
confidence: 99%